Color calibration of multi-view video plus depth for advanced 3D video. Issue 1 (December 2015) - Fezza, Sid; Larabi, Mohamed-Chaker
Abstract Multi-view video plus depth (MVD) format is considered as the next-generation standard for advanced 3D video systems. MVD consists of multiple color videos with a depth value associated with each texture pixel. Relying on this representation and by using depth-image-based rendering techniques, new viewpoints for multi-view video applications can be generated. However, since MVD is captured from different viewing angles with different cameras, significant illumination and color differences can be observed between views. These color mismatches degrade the performance of view rendering algorithms by introducing visible artifacts leading to a reduced view synthesis quality. To cope with this issue, we propose an effective method for correcting color inconsistencies in MVD. Firstly, to avoid occlusion problems and allow performing correction in the most accurate way, we consider only the overlapping region when calculating the color mapping function. These common regions are determined using a reliable feature matching technique. Also, to maintain the temporal coherence, correction is applied on a temporal sliding window. Experimental results show that the proposed method reduces the color difference between views and improves view rendering process providing high-quality results.